Minority rights in the Middle East - Castellino, Joshua; Cavanaugh, Kathleen A. (Oxford : Oxford University Press, 2013)
Minority rights in the Middle East are subject to different legal regimes: national law and international law, as well as Islamic law. This book investigates the treatment of ethnic and religious minorities in the region both from a historical and contemporary perspective, before addressing three case studies Iraq, Syria, and Lebanon.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on June 26, 2013).
Keywords: Human rights -- Middle East; Minorities -- Legal status, laws, etc. -- Middle East